Stereo robust watermark algorithm based on parameter optimization - Yiming XUE; Jinyu ZHANG; Botao CHEN; Zhenghong YANG (Tongxin xuebao)
Aiming at issues such as illegal dissemination of network audio data and privacy leakage, a stereo robust watermark algorithm based on parameter optimization was proposed.Firstly, the watermark was embedded by modifying the singular value ratio of odd segment based on the insensitivity of stereo channels to attack, and aiming at minimizing the relative distortion of the two channels.The embedding process was optimized and the perceived quality of the audio was improved.Then, a parameter optimization method was proposed to find optimal parameters on each audio file, and the imperceptibility and robustness were well balanced.The simulation results show that the proposed algorithm has good imperceptibility and robustness against conventional signal processing.